The Place and the Role of Radiation Therapy in the Treatment of Thymic Carcinoma - Pinelopi-Theopisti, Memtsa (World J Oncol, 2016)
Thymic carcinomas arise from the epithelial cells of the thymus gland and are the most common tumors of the anterior mediastinum despite their overall rarity. Because of their rarity, their treatment remains a challenging topic. Although historically they have been treated surgically, radiation therapy (RT) has an important role either as a definitive or as a postoperative treatment. In this article, we present a review of the current therapies for the thymic carcinomas and try to identify the exact place of the RT in the optimal management of these patients.